The message of Job : suffering and grace - Atkinson, David John, 1943-; Atkinson David (Leicester, England ; Downers Grove, Ill., USA : Inter-Varsity Press, 1991)
The fact of suffering in the world challenges us with its questions. The book of Job is all about human suffering. Its portrayal of one man's sufferings, the ineffective responses of his friends, and his struggle for faith and understanding mirrors our own experiences in the world. David Atkinson offers a pastoral exploration of Job's story. His compelling exposition shows the power of the book of Job to reach into our human situation and to engage with our human needs. It offers, he believes, the strong comfort which comes from knowing that someone else has been there before. The message of Job is both a comfort to us in our own suffering and a model for our ministry to others in pain.
Righteous Job and the wager in heaven (Job 1-3) -- Speeches from Job's friends (see Job 4-27) -- Job's pilgrimage of faith (see Job 4-27; 29-31) -- Wisdom, human and divine (Job 28; 32-37) -- The Lord speaks (Job 38-42).
Includes bibliographical references (page 11).
Keywords: Bible. -- Commentaries